NTERACTIVE EFFECT OF MOISTURE STRESS AND POTASSIUM FERTILIZER LEVEL ON SOME YIELD OF WHEAT (Triticum aestivum L.) - Mohammed, Deia A.; Lateef, Noor Salam (Diyala Agricultural Sciences Journal, 2020)
The experiment was carried out in plastic containers at the experimental fieldof the Agriculture of college , University of Diyala to study the effect of different levels of potassium and water stress on the yield of wheat (Triticum Aestivum L.) class parents 99 for different growth stages .Randomized Complete Block Design (RCBD) in factorial experiment was used .Three levels of Potassium fertilizer added to the soil in form of K2SO4 0, 75, 150 Kg ha-1 , while the treatments of moisture stress ,were a cut Retin non-consecutive terms in three growth stages namely; branch ,elongation and flowering in addition to the continue irrigation without cutting. The results of the study recorded increasing of shoots weight ,total chlorophyll ,number of spikes , spike length ,number of grain, weight of 1000 grains, total grain weight and protein percentage at potassium level of 150 Kg .ha-1 and the values reached 16.74,12.82, 34.83, 22.22, 27.66, 38.27, 80.81, and 22.46 % respectively . Cut irrigation caused reduction of number of spike at branching stage, shoot, and spike length, number of grains at flowering stage which reached 29.19, 49.51, 10.30 and 34.11%.